First Report of Pseudomonas syringae Causing Bacterial Leaf Spot on Winterberry Holly ( Ilex verticillata ) in Ohio - Gutierrez Yanez, Daniela; Emanuel, Isabel Brooke; Roman-Reyna, Veronica; Jacobs, Jonathan Michael; Peduto Hand, Francesca (Plant disease, 2023)
Winterberries ( and hybrids) are deciduous species of holly whose branches bearing colorful fruit are cut in late Fall to be used for seasonal decorations. The annual wholesale value of the woody cuts is $1.5 million nationally (NASS, 2019). In June 2021, approximately 80% of the 45 'Maryland Beauty' potted plants, which were maintained in a container yard at The Ohio State University research farm in Columbus, OH, presented leaves with irregular necrotic lesions surrounded by a chlorotic halo. No other symptoms were present on the plants. Bacterial streaming was observed from the lesions using a compound microscope and isolations were performed after surface disinfesting small sections of leaf tissue from the border of the lesions by soaking in 10% bleach for 30 sec, rinsing twice in sterile water, macerating in sterile water, and streaking the suspension on nutrient broth yeast extract agar. Creamy white, circular, smooth, and convex colonies were recovered after incubation at 28°C for 48 h. Bacterial identification of one representative isolate was initially pursued from single colonies of a purified culture using five discriminative phenotypic tests (i.e., LOPAT: "L", levan production; "O", oxidase activity; "P", pectinolytic activity; "A", arginine dehydrolase production; "T", tobacco hypersensitive reaction), which resulted in the L+ O- P- A- T+ profile consistent with the description of (Lelliott et al. 1996). Molecular identification was performed based on marker amplification and sequencing using primers PsrpoD FNP1/PsrpoDnprpcr1 (Parkison et al. 2011). NCBI GenBank BLASTn comparison of the sequence (GenBank Acc. No. OP221440) shared 99.12% identity to pv. (AB163366.1). Whole genome sequence analysis was conducted to strengthen the classification of the isolate species. To this extent, DNA was sequenced with an iSeq 100 Illumina benchtop sequencer using Illumina DNA Prep kit and iSeq 100 i1 Reagent v2 (Illumina, Inc, REF: 20060060 and 20031371). Illumina Local Run Manager software was used for base calling, demultiplexing, and trimming of the raw reads. Unicycler v0.5.0 was used for assembly of the genome (Wick et al. 2017). The assembled genome size was 5.9 Mb with 959 contigs and 10× coverage (NCBI GenBank Biosample No. SAMN30281368; Acc. No. JANQCB010000000). Average nucleotide identity (ANI) analysis was performed on the server MiGA online (Rodriguez-R et al. 2018). Subgroup identification was inconclusive ( >0.05), positioning this isolate between pv. (96.45% ANI) and pv. (96.65% ANI) (Rodriguez-R & Konstantinidis, 2016). Both these pathovars cause leaf spots on woody plants such as kiwi and viburnum (Donati et al. 2020; Garibaldi et al. 2005). To confirm pathogenicity, three separate branches on each of two 'Maryland Beauty' potted plants were selected, and 5-7 individual young leaves (>2 weeks from emergence) on each branch were infiltrated with a bacterial suspension (10 CFU/mL) in sterile water (SW) using a needleless syringe by delivering 30-50 µL of suspension per infiltration point. One additional branch per plant was infiltrated with SW to serve as control. Plants were covered with a plastic bag for two days post-inoculation (DPI) and maintained in the laboratory at an average of 23°C. All inoculated leaves showed necrotic lesions two DPI while control leaves remained asymptomatic. To fulfill Koch's postulates, the bacterium was re-isolated from the symptomatic leaves six DPI and confirmed to be identical to the original isolate based on gene sequencing. To the best of our knowledge, this report signifies the first instance of causing bacterial leaf spot on winterberry worldwide. Ornamental plant sales are based primarily on visual appeal; therefore, identification and monitoring of emerging pathogens is essential to ensure the health of the industry.